The Meroitic “Initial a” Sign as Griffith’s Initial Aleph - Rowan, Kirsty (Zeitschrift für ägyptische Sprache und Altertumskunde, 2015)
This paper reassesses the sound value of the Meroitic sign traditionally defined as ‘initial a’. This sign is termed ‘initial a’ due to its non-occurrence anywhere other than word-initially in the Meroitic script. A re-evaluation of the evidence for its representation indicates that this sign should be considered as a syllable sign comprised of a glottal stop and the inherent unmarked ‘a’ vowel. Therefore, this sign is likely to be representative of a CV sign, which was one of Griffith’s (1916) proposals, rather than a sign representing only a vowel of varying quality *V, as is currently assumed. As previous proposals for the sound value of this sign have heavily relied on Egyptian transcriptions, this paper reviews the discussions on the Egyptian transcriptions along with the relevant Egyptian phonemic values, and includes a proposal for a sound change process which contributes to the possible revision for the value of this sign.